PENGEMBANGAN MEDIA PEMBELAJARAN BERBASIS SMART APPS CREATOR UNTUK MENINGKATKAN KETERAMPILAN MEMBACA PERMULAAN SISWA KELAS I SD NEGERI 2 ALUE DUA - Ristanti Chikal Larasati; Dini Ramadhani; Juliati (STKIP Subang, 2026)
This study aims to assess the design, validity, practicality, and effectiveness of learning media developed using Smart Apps Creator to support students’ early reading abilities. Conducted at SDN 2 Alue Dua, the research involved 23 first-grade students as the sample group. The methodology employed was Research and Development (R&D), utilizing the ADDIE framework, which includes five core stages: analysis, design, development, implementation, and evaluation. The results showed that the learning media developed with Smart Apps Creator achieved a 98% validation score for content, indicating a very valid category, and an 88% score for media validation, also classified as very valid. In terms of practicality, responses from teachers yielded a score of 99%, while students gave a score of 90%—both falling into the very practical classification. As for effectiveness, the Paired Sample T-test indicated a significance value of 0.001 (p < 0.05), demonstrating a statistically significant difference between pretest and posttest scores. The average score improved from 68.91 before using the media to 86.09 afterward. Furthermore, the calculated N-gain score averaged 0.67, placing it within the medium category of effectiveness.